2014
DOI: 10.1097/ta.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Operation PeaceWorks

Abstract: Epidemiologic study, level III. Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There is increasing evidence that these HVIPs are effective in reducing injury recidivism. 28,32,33 These programs focus on the social circumstances of the patient and modifiable risk factors for recidivism including employment, mental health services, and substance abuse counseling. There is greatest efficacy of these programs when focusing on the highest risk populations such as trauma recidivists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that these HVIPs are effective in reducing injury recidivism. 28,32,33 These programs focus on the social circumstances of the patient and modifiable risk factors for recidivism including employment, mental health services, and substance abuse counseling. There is greatest efficacy of these programs when focusing on the highest risk populations such as trauma recidivists.…”
Section: Discussionmentioning
confidence: 99%
“…There is greatest efficacy of these programs when focusing on the highest risk populations such as trauma recidivists. 28,33 In a randomized control trial of a HVIP assessing patients with recurrent injuries on parole or probation, Cooper et al 28 found lower rates of injury recidivism (5% vs 36%), lower rates of future arrests (Relative Risk 0.4, 95% CI 0.28, 0.67), and higher rates of employment (+43% vs −25%) in the intervention group compared with the control. Additionally, Duncan et al 33 found a 16% decrease in assaults in the area around a given trauma center after the implementation of a program that included mentoring, counseling, job placement, and education components.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other HVIPs successfully addressed the CJ needs of their clients by providing navigators trained to negotiate the CJ system or specially assigned parole and probation officers. 9,48,58 A randomized control trial (RCT) of violently injured patients demonstrated a 39% lower arrest rate for violent crime and 42% lower violent crime conviction for the intervention arm that received a specialized caseworker and probation or parole officer. 9 This RCT's findings suggest HVIPs can offer health benefits to their participants and their communities as well as essential cost- 58 benefits to both the medical and CJ systems.…”
Section: Discussionmentioning
confidence: 99%
“…The general structure includes case management, mentoring for high-risk youth, interruption of violence through conflict mediation, community mobilization, public education, and partnership with public stakeholders such as educators, community organizers, health departments, and faith-based leaders. [12][13][14] There is no currently accepted model that details which of the above program components are most effective, and the programs can be highly variable in their approach, owing to the necessity for them to be informed by the community and local culture. Cure Violence is a public health program that utilizes outreach workers (OWs), to mediate violent conflicts, behaviors, and social norms about violence.…”
mentioning
confidence: 99%
“…Community-based programs employ a similar model, and are highly tailored to the individual needs and culture of each community. The general structure includes case management, mentoring for high-risk youth, interruption of violence through conflict mediation, community mobilization, public education, and partnership with public stakeholders such as educators, community organizers, health departments, and faith-based leaders 12–14 . There is no currently accepted model that details which of the above program components are most effective, and the programs can be highly variable in their approach, owing to the necessity for them to be informed by the community and local culture.…”
mentioning
confidence: 99%